2002
DOI: 10.1021/jp027165+
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Supramolecular Porphyrin-Spacer-Acceptor Ternary Complex and Intracomplex Electron Transfer

Abstract: A new ditopic spacer, N-propylisonicotinamidine, has been developed to assemble a ternary supramolecular complex, zinc-tetraphenylporphyrin (ZnTPP)-spacer-acceptor (3,4-dinitrobenzoic acid), via an axial coordination of the spacer to ZnTPP and a salt bridge interaction between the spacer and acceptor. Formation of this ternary complex was probed by 1 H HMR and UV-vis spectroscopy. The ternary complex is formed with an overall association constant of 1.9 × 10 8 M -2 in dichloromethane. The fluorescence is nearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…These spectral changes are accounted for by the self-association of ZnPA-2 molecules through coordination of the amidine group of one molecule to the zinc ion in another. [20,21] Benzoic acid prevents this self-association of ZnPA-2 by forming the amidinium-carboxylate salt bridge with ZnPA-2. Thus, upon addition of benzoic acid to a solution of ZnPA-2, the spectrum reverted to the one for isolated ZnPA-2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These spectral changes are accounted for by the self-association of ZnPA-2 molecules through coordination of the amidine group of one molecule to the zinc ion in another. [20,21] Benzoic acid prevents this self-association of ZnPA-2 by forming the amidinium-carboxylate salt bridge with ZnPA-2. Thus, upon addition of benzoic acid to a solution of ZnPA-2, the spectrum reverted to the one for isolated ZnPA-2.…”
Section: Resultsmentioning
confidence: 99%
“…Keywords: energy transfer · porphyrinoids · salt bridges · supramolecular chemistry · through-bond interactions porphyrin connected through an amidinium-carboxylate salt bridge. [13][14][15][16][17][18][19][20][21][22][23] The same intermolecular bond was also used for the construction of an antenna-type (donor) 4 ·A C H T U N G T R E N N U N G (acceptor) complex. We found that the rates of excited energy-transfer processes in these supramolecules are much larger than expected from the Fçrster-type energy-transfer mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach for the study of PCET across amidinium-carboxylate interfaces relies on the formation of ternary complexes such as that shown for 16 [141]. A N-propylisonicotinamidine serves as a ditopic spacer between a Zn II tetraphenylporphyrin donor and 3,4-dinitrobenzoate acceptor.…”
Section: Pcet Across Polarized Hydrogen Bonding Interfacesmentioning
confidence: 99%
“…As discussed previously, this approach can be problematic because the dynamics of fluorescence decay are not necessarily specific to charge transport. Furthermore, PCET can proceed from non-emitting states to which time resolved emission spectroscopy is blind [105,141]. Accordingly, there is great benefit offered by systems that allow the PCET kinetics to be determined directly from observed charge transport intermediates.…”
Section: Pcet Model System [A]mentioning
confidence: 99%
“…Both the fluorescence and the triplet excited state of ZnP are nearly completely quenched by the electron acceptor in the ternary complex. Photoinduced intracomplex electron transfer is invoked as a likely mechanism of the fluorescence quenching and triplet bleaching [8].…”
Section: Metal Coordinationmentioning
confidence: 99%